The Effect Of Learning Management System Quality, Interactive Learning Features And Organizational Support On Digital Learning Adoption Of Vocational High School Students - Mohzana; Sagaf S. Pettalongi; Muhammad Arsyad; Rio Haribowo; Ilham Arief; Agus Rofi'i (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
The research investigates how Learning Management System quality together with interactive learning features and organizational support affects Indonesian vocational high school students ability to adopt digital learning technology. Digital learning adoption functions as a vital component which enables vocational education programs to meet the demands of a technology-based job market. The researchers used a quantitative research approach which employed an explanatory research framework. The researchers obtained primary data through questionnaires which they delivered to vocational high school students who studied through Learning Management Systems. The researchers used purposive sampling to select respondents who had previous experience with digital learning experiences as their study requirement. The researchers used multiple linear regression analysis to examine how various study variables influenced each other during the research process. The research findings demonstrated that Learning Management System quality together with interactive learning features and organizational support produced a significant impact on digital learning adoption when assessed through their combined assessment. The three independent variables exhibited positive and significant effects on the level of digital learning adoption according to the study results. The research results demonstrate that technological elements together with interactive capabilities and organizational backing function as essential factors which enable effective digital learning implementation. Schools need to improve their digital learning system quality through development of better interactive features and greater organizational support to achieve digital learning adoption.